الضبط الاداري البيئي آلية لتفرد الدولة لحماية البيئة في الجزائر - عبنة,قيس (University of Eloued جامعة الوادي, 2023)
إن النموذج التنموي الذي اعتمدته الجزائر بعد الاستقلال والذي يرتكز على التصنيع والصناعات الثقيلة، أثبت عدم احترامه لأدنى معايير حماية البيئة، مما تطلب منها مباشرة الإصلاحات مع إلزامية إعطاء الأولوية للجانب البيئي وتدارك الإخفاقات من خلال سن الآليات القوانين التي من شأنها الحد من التلوث البيئي الناتج عن المشاريع التنموية، فأقامت هيئات فنية متخصصة في مجال حماية البيئة تعمل على إيجاد كافة الحلول للمشكلات البيئية والحفاظ عليها وتكريس مبدأ النشاط الوقائي قبل حدوث الأضرار البيئية، وللحد من التدهور البيئي تدخل المشرع بعدة أساليب وآليات قانونية تستوقفنا في هذه الدراسة من خلال تسليط الضوء عليها وتميزها بحسب موضوعها وتوقيتها، حيث يمكن أن تكون تلك المعالجة بأساليب إدارية بحتة يطغى عليها الطابع الاحتكاري الوقائي للإدارة العامة وهي ما يصطلح عليها بالضبط الاداري البيئي. Abstract: The development model adopted by Algeria after independence, which is based on industrialization and heavy industries, proved its lack of respect for the lowest standards of environmental protection, which required it to initiate reforms with the obligation to give priority to the environmental aspect and remedy failures through the enactment of mechanisms and laws that would reduce environmental pollution resulting from Development projects, it established technical bodies specialized in the field of environmental protection working to find all solutions to environmental problems and preserve them and devote the principle of preventive activity before the occurrence of environmental damage, and to reduce environmental degradation, the legislator intervened in several legal methods and mechanisms that stop us in this study by highlighting them and distinguishing them according to Its subject and timing, as this treatment can be purely administrative methods that are dominated by the preventive monopolistic nature of public administration, which is what is termed exactly environmental administrative.
Keywords: الضبط الاداري البيئي; التدهور البيئي; حماية البيئة; environment; environmental administrative control; environmental degradation; environment protection